Pengaruh Profitabilitas Dan Solvabilitas Terhadap Kebijakan Dividen Pada Sektor Consumer Non Cylicals Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2024: Pengaruh Profitabilitas Dan Solvabilitas Terhadap Kebijakan Dividen Pada Sektor Consumer Non Cylicals Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2024 - Dwi Intan Muharani; Rani Rani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study was conducted to investigate the impact of profitability and solvency on dividend policy in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This sector was chosen because of its important role in the national economy, particularly given its relatively stable characteristics in the face of global economic dynamics, as seen in the production of staple goods. The independent variables in this study are profitability, proxied by Return on Assets (ROA), and solvency, proxied by the Debt to Asset Ratio (DAR). The dependent variable is dividend policy, measured by the Dividend Payout Ratio (DPR). The research method used is a quantitative approach with a causal associative design. The study population includes all non-cyclical consumer companies listed on the IDX, while the sample was obtained through a purposive sampling method with certain criteria. The data used are secondary data sourced from the companies' annual financial reports. Data analysis was performed using multiple linear regression with the help of SPSS version 27 software, and tested with the classical assumption test, partial test (t-test), simultaneous test (F-test), and coefficient of determination. The research results show that profitability has no significant effect on dividend policy. Similarly, solvency has no significant effect on dividend policy. Simultaneous testing also showed that both variables together had no significant effect on dividend policy. This finding indicates that dividend distribution decisions are more influenced by other factors, such as investment needs, cash flow, and internal company policies. Theoretically, this study supports the concept of residual dividend policy and pecking order theory, which emphasize the importance of using profits to fund investments and maintain financial stability before distributing dividends. Therefore, it can be concluded that profitability and solvency are not dominant factors in determining dividend policy in the non-cyclical consumer sector.